Classification of Nepalese Forests and Their Distribution in Protected Areas - Shrestha, Tirtha Bahadur (The Initiation, 2010)
Nepal is nature's paradise. It's a small attractive package of nature embracing the rich biological diversity in the tiniest area. One of the nature's gifts to Nepal is its vegetation. The narrow strip of land harbours over 170 parcels of vegetation. The need of categorisation of Nepal's forest type is thus not only needed to acknowledge the rich diversity but also to make it applicable in scientific studies and researches. This paper endeavours to classify the Nepal's forest according to all the rational parameters yet avoiding the strict compartmentalisation which is near to impossible as in the case of natural and life bearing heritage like forest. Key Words: Forest type, Ecological map, Classification, Protected areas DOI: 10.3126/init.v2i1.2512 The Initiation Vol.2(1) pp1-9